Records Utilization and Service Delivery in The Central Registry at Kabale District Local Government. - Namanya, Ovet (Kabale University, 2023)
The purpose of the study was to assess records utilization and service delivery in the Central Registry at Kabale District Local Government. In light of the aim of the study, the following objectives were to; find out the categories of records maintained at the Central Registry at Kabale District local Governance, to establish the challenges faced in the utilization of records at Central Registry at Kabale District local governance and to suggest the possible solutions to the identified challenges faced in the utilization of records and service delivery at Central Registry at Kabale District local governance. The study employed a Descriptive research design that was used in gathering information. Both Qualitative and Quantitative data were collected and this enabled the researcher to draw valid and dependable conclusions and recommendations. The researcher selected a sample of 3 7 respondents who represented the whole study Population using Purposive sampling. 4 staff members working in different departments, 2 records officers, and 31 clients will be selected from Kabale District Local Government Headquarters. The findings from the study revealed that there are categories of records maintained by District Central Registries among others, including Administration and withdrawal register records, financial records, and administrative records. The findings from the study revealed that there are challenges faced in the Utilization of records at the Central Registry at Kabale District Local Government such as high relative humidity, abuse, mishandling, and lack of enough funds to support the management of records. The findings from the study revealed that there is still hope and records deterioration at the Central Registry at Kabale District Local Government can be controlled through the application of, the use of acid-free equipment and papers. The researcher recommends that there should be an establishment of records retention and disposal schedules. These schedules set out instructions for transferring records from all departments to the records office. The schedules should also provide instructions for the eventual disposal of the records, either by destruction or by transfer to the archival, repository